2022
DOI: 10.3390/ijerph192114071
|View full text |Cite
|
Sign up to set email alerts
|

Child Welfare Reform: A Scoping Review

Abstract: While there have been ongoing calls to reform child welfare so that it better meets children’s and families’ needs, to date there have been no comprehensive summaries of child welfare reform strategies. For this systematic scoping review, we summarized authors’ recommendations for improving child welfare. We conducted a systematic search (2010 to 2021) and included published reviews that addressed authors’ recommendations for improving child welfare for children, youth, and families coming into contact with ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 202 publications
0
4
0
Order By: Relevance
“…Providers need to consider these principles at all phases of assessment and intervention, including when doing a case conceptualization. Some of these principles include the need for support and services to be evidence-based; tailored to the specific family/child including to the child’s age and stage of development; culturally sensitive; trauma-informed; comprehensive; and strengths-based ( 21 ). For example, principles of trauma-informed practice are increasingly incorporated into core competencies for healthcare and social service providers supporting children and families involved in child welfare ( 22–24 ).…”
Section: The Importance Of Trauma- and Violence-informed Carementioning
confidence: 99%
“…Providers need to consider these principles at all phases of assessment and intervention, including when doing a case conceptualization. Some of these principles include the need for support and services to be evidence-based; tailored to the specific family/child including to the child’s age and stage of development; culturally sensitive; trauma-informed; comprehensive; and strengths-based ( 21 ). For example, principles of trauma-informed practice are increasingly incorporated into core competencies for healthcare and social service providers supporting children and families involved in child welfare ( 22–24 ).…”
Section: The Importance Of Trauma- and Violence-informed Carementioning
confidence: 99%
“…The literature review found that most screening instruments focus on specific domains of child development, while a broad perspective is needed for adequate assessment and identification of solutions [12,[29][30][31][32]. The child's well-being often depends on their parents and cannot be assessed in isolation from the care needs of parents.…”
Section: Content Criteriamentioning
confidence: 99%
“…Over the last two decades, Ghana, along with a number of LMICs, has redesigned its childcare system with a focus on deinstitutionalization, which has become a global norm in alternative care for children (Frimpong‐Manso, 2014; McTavish et al, 2022). Deinstitutionalization (DI) refers to the policy of dismantling or reforming large institutions in favour of family‐based and family‐like care for children in the community (Goldman et al, 2020; Terziev & Arabska, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Quality residential care, provided in small family-like settings, could serve as a measure of last resort for specific groups of children. UNGAC's recommendations are based on a large body of research evidence showing the negative effects of institutionalization on children's general well-being, health and developmental outcomes (van IJzendoorn et al, 2020).Over the last two decades, Ghana, along with a number of LMICs, has redesigned its childcare system with a focus on deinstitutionalization, which has become a global norm in alternative care for children (Frimpong-Manso, 2014;McTavish et al, 2022). Deinstitutionalization (DI) refers to the policy of dismantling or reforming large institutions…”
mentioning
confidence: 99%